2009
DOI: 10.1016/j.psychres.2008.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Impulsivity and clinical symptoms among adolescents with non-suicidal self-injury with or without attempted suicide

Abstract: This study examined clinical characteristics and laboratory-measured impulsive behavior of adolescents engaging in either non-suicidal self-injury with (NSSI+SA; n = 25) or without (NSSIOnly; n = 31) suicide attempts. We hypothesized that adolescent with NSSI+SI would exhibit more severe clinical symptoms and higher levels of behavioral impulsivity compared to adolescents with NSSI-Only. Adolescents were recruited from an inpatient psychiatric hospital unit and the two groups were compared on demographic chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
102
2
14

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(127 citation statements)
references
References 38 publications
9
102
2
14
Order By: Relevance
“…More depressive symptoms (Dougherty et al, 2009;Jacobson et al, 2008;Muenhlenkamp & Gutierrez, 2007;Taliaferro, Muehlenkamp, Borowsky, McMorris, & Kugler, 2012), hopelessness (Dougherty et al, 2009;Taliaferro et al, 2012), suicidal ideation (Brausch & Gutierrez, 2010;Dougherty et al, 2009;Muehlenkamp & Gutierrez, 2007) and history of physical abuse (Asarnow et al, 2011;Taliaferro et al, 2012) were found in the NSSI+SA group compared to the NSSI group in both community and clinical and samples. In addition, fewer reasons for living (Muehlenkamp & Gutierrez, 2007) and less parental support (Brausch & Gutierrez, 2010) have also been reported by individuals with NSSI+SA in community samples.…”
Section: Non-suicidal and Suicidal Self-injurymentioning
confidence: 99%
“…More depressive symptoms (Dougherty et al, 2009;Jacobson et al, 2008;Muenhlenkamp & Gutierrez, 2007;Taliaferro, Muehlenkamp, Borowsky, McMorris, & Kugler, 2012), hopelessness (Dougherty et al, 2009;Taliaferro et al, 2012), suicidal ideation (Brausch & Gutierrez, 2010;Dougherty et al, 2009;Muehlenkamp & Gutierrez, 2007) and history of physical abuse (Asarnow et al, 2011;Taliaferro et al, 2012) were found in the NSSI+SA group compared to the NSSI group in both community and clinical and samples. In addition, fewer reasons for living (Muehlenkamp & Gutierrez, 2007) and less parental support (Brausch & Gutierrez, 2010) have also been reported by individuals with NSSI+SA in community samples.…”
Section: Non-suicidal and Suicidal Self-injurymentioning
confidence: 99%
“…O início da automutilação geralmente acontece na adolescência, entre os 11 e 15 anos e pode permanecer por décadas (Favazza, 1998;LayeGindhu;Sohonest-Reichll, 2005;Klonsky, 2007b, Dougherty et al, 2009Kerr;Muehlenkamp, 2010;Catledge et al, 2012;Swannell et al, 2014).…”
Section: Prevalênciaunclassified
“…A impulsividade tem sido considerada como um importante componente para se compreender a automutilação (Simeon et al, 1992;Herpertz et al, 1995;Herpertz et al, 1997;Dougherty et al, 2009). O termo impulsividade, como característica, traço ou definição de um tipo de personalidade, tem sido utilizado para abordar os aspectos impulsivos de alguns transtornos.…”
Section: T=transtornosunclassified
See 1 more Smart Citation
“…Ce résultat a été répliqué depuis chez des adolescents (Dougherty et al, 2009 ;Mathias et al, 2011) Il a aussi été mis en évidence une prise de décision désavantageu-se chez le sujet âgé suicidant (Clark et al, 2011, Dombrovski et al, 2011b, suggérant que les anomalies de prise de décision peuvent être un facteur cognitif de vulnérabilité suicidaire à tout âge.…”
Section: La Prise De Décisionunclassified